2017
DOI: 10.3390/data2030028
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Data Set of Pesticide Dissipation Rates in/on Various Plant Matrices for the Pesticide Properties Database (PPDB)

Abstract: Data relating to the rate at which pesticide active substances dissipate on or within various plant matrices are important for a range of different risk assessments; however, despite the importance of this data, dissipation rates are not included in the most common online data resources. Databases have been collated in the past, but these tend not to be maintained or regularly updated. The purpose of the exercise described herein was to collate a new database in a format compatible with the main online pestici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…An extensive database of pesticide dissipation is available on the web. Lewis et al [20] developed a dataset of pesticide dissipation rates in/on various plant matrices for the Pesticide Properties Database (PPDB). The influence of the specific part of the plant is highlighted, the leaves being the part that showed the greatest variations in the pesticide dissipation rates.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive database of pesticide dissipation is available on the web. Lewis et al [20] developed a dataset of pesticide dissipation rates in/on various plant matrices for the Pesticide Properties Database (PPDB). The influence of the specific part of the plant is highlighted, the leaves being the part that showed the greatest variations in the pesticide dissipation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is believed that—when applied incorrectly—most fungicides may lead to disorders in the metabolism of microorganisms, which is in turn reflected in the activities of soil enzymes [ 45 , 46 ]. In addition, the suppressed activity of certain soil enzymes may be due to their immobilization by soil colloids or to a small amount of organic matter in the soil [ 38 , 47 ]. The adverse effect of tebuconazole applied in doses of 5.0, 50.0, and 500 mg kg −1 on the activities of urease, alkaline phosphatase, β-glucosidase, and arylsulfatase was reported by Muñoz-Leoz et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the instability of oxydemetonmethyl in walnut trees for long periods of time and the non-toxicity of its metabolites for leopard moth larvae. Investigations have reported that the half-life of Oxydemeton-methyl is 30-40 days (Lewis & Tzilivakis, 2017).…”
Section: Mean Effectiveness (%)mentioning
confidence: 99%